Offshore Geothermal Energy Perspectives: Hotspots and Challenges - Paulo H. Gulelmo Souza; Alexandre Szklo (Resources, 2025)
Geothermal energy is a low-carbon and reliable energy resource capable of generating both heat and electricity from the Earth’s internal thermal energy. While geothermal development has traditionally been focused on onshore sites, offshore geothermal resources are attracting growing interest due to advancements in technology, the search for alternative baseload power, and the opportunity to repurpose decommissioned petroleum infrastructure. Recent efforts include utilizing abandoned oil and gas fields to adapt existing infrastructure for geothermal use, as well as exploring high-temperature geothermal zones such as submarine volcanoes and hotspots. Despite these initiatives, research output, scientific publications and patents remain relatively limited, suggesting that offshore geothermal technology is still in its early stages. Countries like Italy, Indonesia and Turkey are actively investigating geothermal resources in volcanic marine areas, while North Sea countries and the USA are assessing the feasibility of converting mature oil and gas fields into geothermal energy sites. These diverse strategies underscore the regional geological and infrastructure conditions in shaping development approaches. Although expertise from the oil and gas industry can accelerate technological progress in marine geothermal energy, economic challenges remain. Therefore, improving cost competitiveness is crucial for offshore geothermal energy.